2010
DOI: 10.3109/00016481003782033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Meniett®treatment on hearing

Abstract: PTA values increased on average by 7.1 dB (95% CI = 2.7-11.5; p = 0.003) during the time period from the beginning of the treatment to the end of the follow-up. Q scores decreased on average by 20.6 (95% CI = 8.8-32.4; p < 0.001) during the pre- and post-Meniett® time-span. These two outcomes appeared not to influence each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many therapeutic approaches to Meniere’s disease have been studied. These include a low salt diet and diuretics,8 intratympanic steroid application,9 10 or minimal invasive interventions (such as insertion of a ventilation tube into the tympanic membrane,11 12 endolymphatic sac surgery,13 or pulsed low pressure delivery (using Meniett devices)) 1415 16 17 For patients who do not respond to these treatments, more aggressive procedures can be considered, such as intratympanic application of gentamycin,18 19 plugging of the semicircular canal, labyrinthectomy, or neurectomy 20…”
Section: Introductionmentioning
confidence: 99%
“…Many therapeutic approaches to Meniere’s disease have been studied. These include a low salt diet and diuretics,8 intratympanic steroid application,9 10 or minimal invasive interventions (such as insertion of a ventilation tube into the tympanic membrane,11 12 endolymphatic sac surgery,13 or pulsed low pressure delivery (using Meniett devices)) 1415 16 17 For patients who do not respond to these treatments, more aggressive procedures can be considered, such as intratympanic application of gentamycin,18 19 plugging of the semicircular canal, labyrinthectomy, or neurectomy 20…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies reported PTA before and after Meniett treatment, eight studies reported frequency of vertigo before and after treatment, and seven studies reported the AAO‐HNS functional score before and after treatment . Egger tests for all three study sets showed that there was no significant publication biases among these studies for PTA (P = 0.33), AAO‐HNS function score ( P = 0.48), and frequency of vertigo ( P = 0.07).…”
Section: Resultsmentioning
confidence: 95%
“…Figure shows the flow chart of the search results. Of 113 studies identified, 18 studies met criteria for a thorough review . Table and Table provide the characteristics of the 18 studies (type of study, number of patients, PTA before and after Meniett treatment, vertigo scores before and after treatment).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation